Primary mediastinal germ cell tumors: Survival outcomes and prognostic factors – 10 years experience from a tertiary care institute - Kumar, Narendra (Rare Tumors, 2020)
Primary Mediastinal Germ Cell Tumor (PMGCT) is a rare and heterogeneous entity. These tumors are typically diagnosed in young adults and carry a poor prognosis. We conducted this study to evaluate the role of radiotherapy on treatment outcomes and prognostic factors in PMGCT that may allow a more adapted treatment strategy to improve survival. Case records of patients who presented with PMGCT over a period of 10-years from January-2009 to December-2019 were retrospectively evaluated. Survival analyses were calculated using Kaplan-Meier (Log-rank) method. Poor prognostic factors for survival were evaluated with Multivariate analysis using Cox-regression method. A total of 46-patients data was analyzed, the majority of the patients were males (95.7%) with a median age of 25-years (range, 17–62). Non-seminomatous histology was predominant (60.9%). Sixteen-patients (34.7%) presented with complications at their initial presentation. Majority of the patients were treated with multimodality approach using chemotherapy, surgery, and/or radiotherapy. At a median follow-up of 40.8 months, the 1, 3, and 5-year overall survival (OS) was 69.6%, 52.2%, and 44.7% respectively. Patients who received radiotherapy in first-line treatment showed significant improvement in 5-year OS (72% vs 30%, p = 0.004) and disease-free survival (70% vs 24%, p = 0.007) in comparison with patients who did not receive. Multivariate analysis revealed that radiotherapy, chemotherapy, surgery, and complications at presentation were independent prognostic factors for OS. PMGCTs are aggressive neoplasms especially in patients presenting with disease-related complications. Dual modality management (radiotherapy as local therapy along with chemotherapy) had shown improvement in survival.